Identification of hydropedological flowpaths in Stevenson–Hamilton catena from soil morphological, chemical and hydraulic properties - Darren Bouwer; Pieter A.L. le Roux; Johan van Tol (Koedoe: African Protected Area Conservation and Science, 2020)
In highly variable water regimes of semi-arid savannahs, water is the key driving force for biotic and abiotic processes. Understanding and measuring components of the hydrological cycle at landscape scale is however difficult because of the spatiotemporal variation of these processes. Hydropedology is a new interdisciplinary research field aiming to use soil information to conceptualise hydrological processes at different scales. In this study, a hydropedological approach was used to identify key hydrological flowpaths on a granitic catena in the Stevenson–Hamilton Supersite in the Kruger National Park. Soils from 49 plots, spaced 10 m apart along a catena, were classified, and their morphology was interpreted in relation to the dominant hydrological response. Soil samples were taken at 10-cm-depth intervals for chemical and physical analysis to assess the relationship between their expected hydrological behaviour and physiochemical properties. The hydropedological survey indicated that the crest is dominated by freely drained recharge soils where infiltration and vertical drainage are dominant. On the midslope, the underlying bedrock has restricted permeability; this promotes lateral flow at the soil/bedrock interface. On the upper footslope, high clay content soils (sodic) restricts further lateral drainage, resulting in return flow (seepage). Overland flow is dominant on the upper and lower footslope. The valley bottom is occupied by freely drained alluvial soils, which act as a recharge zone. The chemical and physical analyses of soil support the interpretations of the hydropedological interpretation of the soil morphology. Conservation implications: Understanding hydrological processes is important for sustainable water resource management, especially in the areas with highly variable water regimes. A hydropedological approach provides an efficient method to characterise dominant flowpaths at landscape scale. This aids the estimation of the hydrological sensitivity of the landscape to climate and land use changes.